The HPr(Ser) Kinase of Streptococcus salivarius: Purification, Properties, and Cloning of the hprK Gene - Brochu, Denis (American Society for Microbiology, 1999)
In gram-positive bacteria, HPr, a protein of the phosphoenolpyruvate:sugar phosphotransferase system, is phosphorylated on a serine residue at position 46 by an ATP-dependent protein kinase. The HPr(Ser) kinase of Streptococcus salivarius ATCC 25975 was purified, and the encoding gene (hprK) was cloned by using a nucleotide probe designed from the N-terminal amino acid sequence. The predicted amino acid sequence of the S. salivarius enzyme showed 45% identity with the Bacillus subtilis enzyme, the conserved residues being located mainly in the C-terminal half of the protein. The predicted hprK gene product has a molecular mass of 34,440 Da and a pI of 5.6. These values agree well with those found experimentally by polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate, molecular sieve chromatography in the presence of guanidine hydrochloride, and chromatofocusing using the purified protein. The native protein migrates on a Superdex 200 HR column as a 330,000-Da protein, suggesting that the HPr(Ser) kinase is a decamer. The enzyme requires Mg(2+) for activity and functions optimally at pH 7.5. Unlike the enzyme from other gram-positive bacteria, the HPr(Ser) kinase from S. salivarius is not stimulated by FDP or other glycolytic intermediates. The enzyme is inhibited by inorganic phosphate, and its K(m)s for HPr and ATP are 31 μM and 1 mM, respectively.